Gate-tunable photodetector and ambipolar transistor implemented using a graphene/MoSe2 barristor - Oh, Gwangtaek; Jeon, Ji Hoon; Kim, Young Chul; Ahn, Yeong Hwan; Park, Bae Ho (NPG Asia Materials, 2021)
Next-generation electronic and optoelectronic devices require a high-quality channel layer. Graphene is a good candidate because of its high carrier mobility and unique ambipolar transport characteristics. However, the on/off ratio and photoresponsivity of graphene are typically low. Transition metal dichalcogenides (e.g., MoSe2) are semiconductors with high photoresponsivity but lower mobility than that of graphene. Here, we propose a graphene/MoSe2 barristor with a high-k ion-gel gate dielectric. It shows a high on/off ratio (3.3 × 104) and ambipolar behavior that is controlled by an external bias. The barristor exhibits very high external quantum efficiency (EQE, 66.3%) and photoresponsivity (285.0 mA/W). We demonstrate that an electric field applied to the gate electrode substantially modulates the photocurrent of the barristor, resulting in a high gate tuning ratio (1.50 μA/V). Therefore, this barristor shows potential for use as an ambipolar transistor with a high on/off ratio and a gate-tunable photodetector with a high EQE and responsivity.
Keywords: Ambipolar behavior; Ambipolar transistors; Ambipolar transport; External quantum efficiency; High carrier mobility; Photoresponsivity; Transition metal dichalcogenides; Tunable photodetectors